OREXIN 1 AND 2 RECEPTOR INVOLVEMENT IN CO2‐INDUCED PANIC‐ASSOCIATED BEHAVIOR AND AUTONOMIC RESPONSES. Issue 9 (19th August 2015) - Johnson, Philip L.; Federici, Lauren M.; Fitz, Stephanie D.; Renger, John J.; Shireman, Brock; Winrow, Christopher J.; Bonaventure, Pascal; Shekhar, Anantha
Abstract : Background: The neuropeptides orexin A and B play a role in reward and feeding and are critical for arousal. However, it was not initially appreciated that most prepro‐orexin synthesizing neurons are almost exclusively concentrated in the perifornical hypothalamus, which when stimulated elicits panic‐associated behavior and cardiovascular responses in rodents and self‐reported "panic attacks" and "fear of dying" in humans. More recent studies support a role for the orexin system in coordinating an integrative stress response. For instance, orexin neurons are highly reactive to anxiogenic stimuli, are hyperactive in anxiety pathology, and have strong projections to anxiety and panic‐associated circuitry. Although the two cognate orexin receptors are colocalized in many brain regions, the orexin 2 receptor (OX2R) most robustly maps to the histaminergic wake‐promoting region, while the orexin 1 receptor (OX1R) distribution is more exclusive and dense in anxiety and panic circuitry regions, such as the locus ceruleus. Overall, this suggests that OX1Rs play a critical role in mobilizing anxiety and panic responses. Methods: Here, we used a CO2 ‐panic provocation model to screen a dual OX1/2R antagonist (DORA‐12) to globally inhibit orexin activity, then a highly selective OX1R antagonist (SORA1, Compound 56) or OX2R antagonist (SORA2, JnJ10397049) to assess OX1R and OX2R involvement. Results: All compounds except the SORA2 attenuated CO2 ‐induced anxiety‐like behaviors, and all but the SORA2 and DORA attenuated CO2 ‐induced cardiovascular responses. Conclusions: SORA1s may represent a novel method of treating anxiety disorders, with no apparent sedative effects that were present with a benzodiazepine.